Enhancing Forensic Processes with Quantum Cryptographic Techniques: A Comprehensive Investigation - Shyam Narayan Singh; Vinny Sharma; Nikhil Khapra; Tushar Mathpal (Indian Journal of Forensic Medicine and Pathology, 2025)
Every day, forensic investigators find themselves buried under an avalanche of digital evidence, terabytes of files, logs, and signals that can make even the most seasoned analyst feel overwhelmed. At the same time, cybercriminals are sharpening their tools, probing weaknesses in traditional encryption, and leaving us vulnerable just when we need airtight security most. Enter quantum cryptography: a radical shift in how we protect information, where the very laws of physics guard our data. Quantum Key Distribution (QKD) uses delicate photons to forge encryption keys that, if tampered with, immediately betray an eavesdropper’s presence. Alongside this, post-quantum cryptographic schemes promise software defenses that even future quantum computers can’t crack.1 In this review, we’ll walk you through how these quantum-powered techniques can transform three critical stages of forensic work: capturing evidence without fear of interception, preserving an unbreakable chain of custody, and verifying data integrity long after a case closes. You’ll learn about the nuts and bolts of QKD networks,2 the latest in quantum-resistant algorithms, and how hybrids of the two can give investigators both immediate and future-proof protection. We’ll also tackle the real-world hurdles, bulky hardware, system integration headaches, and the need for common standards, and point toward research paths and practical roadmaps that could bring quantum-secure forensics into every lab